Persepsi Orang Tua Siswa Terhadap Biaya Pendidikan - Dewi, Putu Yulia Apsari; Indrayani, Luh (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2021)
The cost spent on education fee cannot be considered low, especially in big cities like Singaraja City. Education fee still becomes a major consideration for people to obtain an education, particularly for those who have low economic background. This problem certainly requires government’s help. Since 2005, the government has distributed educational funding through BOS funds. The problem occurs because BOS fund is only sufficient to fulfill the educational operations, it cannot cover all personal costs that must be spent to fulfill students’ needs in school. This arises various perceptions from students’ parents, both positive and negative. Therefore, this study aimed to determine how parents' perceptions towards education fee, especially in Singaraja City. This research implemented descriptive qualitative approach. The results of this study concluded how high school students’ parents’ perceptions towards the educational fee in Singaraja city. In general, parents argue that there are still many costs that they spend despite receiving BOS funding. Nevertheless, they do not mind spending certain cost for education purposes because they realize that education is important for their children’s future.